Bushehr Elderly Health (BEH) Programme, phase I (cardiovascular system). Issue 12 (16th December 2015) - Ostovar, Afshin; Nabipour, Iraj; Larijani, Bagher; Heshmat, Ramin; Darabi, Hossein; Vahdat, Katayoun; Ravanipour, Maryam; Mehrdad, Neda; Raeisi, Alireza; Heidari, Gholamreza; Shafiee, Gita; Haeri, Mohammadjavad; et al.
Abstract : Purpose: The main objective of the Bushehr Elderly Health Programme, in its first phase, is to investigate the prevalence of cardiovascular risk factors and their association with major adverse cardiovascular events. Participants: Between March 2013 and October 2014, a total of 3000 men and women aged ≥60 years, residing in Bushehr, Iran, participated in this prospective cohort study (participation rate=90.2%). Findings to date: Baseline data on risk factors, including demographic and socioeconomic status, smoking and medical history, were collected through a modified WHO MONICA questionnaire. Vital signs and anthropometric measures, including systolic and diastolic blood pressure, weight, height, and waist and hip circumference, were also measured. 12-lead electrocardiography and echocardiography were conducted on all participants, and total of 10 cc venous blood was taken, and sera was separated and stored at –80°C for possible future use. Preliminary data analyses showed a noticeably higher prevalence of risk factors among older women compared to that in men. Future plans: Risk factor assessments will be repeated every 5 years, and the participants will be followed during the study to measure the occurrence of major adverse cardiac events. Moreover, the second phase, which includes investigation of bone health and cognition in the elderly, was started in September 2015. Data are available at the Persian Gulf Biomedical Research Institute, Bushehr University of Medical Sciences, Bushehr, Iran, for any collaboration.